2018
DOI: 10.3390/app8112089
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning Case Study for Automatic Bird Identification

Abstract: An automatic bird identification system is required for offshore wind farms in Finland. Indubitably, a radar is the obvious choice to detect flying birds, but external information is required for actual identification. We applied visual camera images as external data. The proposed system for automatic bird identification consists of a radar, a motorized video head and a single-lens reflex camera with a telephoto lens. A convolutional neural network trained with a deep learning algorithm is applied to the image… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 14 publications
0
13
0
2
Order By: Relevance
“…In addition to the CNN model introduced above, we have tested the svm-on-top model, which has otherwise the same structure as this CNN model, but an svm classifier was connected to the second fully connected layer. 22 However, the tests for this study showed that the classification performance is the same or even slightly better when using only the CNN. Moreover, the svm-on-top model had significantly longer training time than the CNN model alone.…”
Section: Tested Cnn Structures and Hyperparameter Selectionmentioning
confidence: 61%
See 3 more Smart Citations
“…In addition to the CNN model introduced above, we have tested the svm-on-top model, which has otherwise the same structure as this CNN model, but an svm classifier was connected to the second fully connected layer. 22 However, the tests for this study showed that the classification performance is the same or even slightly better when using only the CNN. Moreover, the svm-on-top model had significantly longer training time than the CNN model alone.…”
Section: Tested Cnn Structures and Hyperparameter Selectionmentioning
confidence: 61%
“…21 For more details, see previous studies. 19,22 A number of images for each species (classes) in the augmented dataset when s = 50 and s = 200, respectively, are presented in Table 2 .…”
Section: Data Augmentationmentioning
confidence: 99%
See 2 more Smart Citations
“…AI which encapsulates Machine learning (ML) [14] and Deep leaning (DNN) [15] show up in countless articles out of the technology motivated ones. A Deep neural network as proposed by [15,16] has the potential of estimating both continuous and discrete function. Recently, various application areas such as speech recognition, computer vision and text processing [17] among other fields have experienced the potency of deep neural networks.…”
Section: Review Of Related Workmentioning
confidence: 99%